Ocorrência de nitrato em águas subterrâneas na Unidade de Gerenciamento de Recursos Hídricos Tietê-Jacaré - Casagrande, Lucas Antonio Ribas (Universidade Federal de São Carlos, 2012)
Agricultural practices present themselves as potentially polluting to groundwater. The recharge areas, where the aquifers tend to be more vulnerable, are under important agricultural areas, and there are not many researches that evaluate the impact of agricultural activity on groundwater quality. The occurrence of high nitrate concentrations, as an effect of the intensive use of fertilizers and nitrogen-rich agricultural products, along with the disposal of agro-industrial residues on the ground, such as nitrogen-rich vinasse, are some of the biggest concerns due to agricultural activity. Considering the existence of extensive areas of sugar cane production, as well as the need for preserving the recharge areas occurring at the Water Resources Management Unit nº 13 (Tietê-Jacaré), this research has as its main goal the accomplishment of a survey and systematization, from water quality existing data, of nitrate occurrence in Serra Geral, Bauru and Guarani Aquifer Systems groundwater, at the Tietê- Jacaré hydrographic basin. Thus, the existing data from groundwater quality monitoring performed by the São Paulo State Environmental Agency were consolidated, for the nitrate parameter, and, moreover, there had been analyzed results from groundwater analyses, for the Nitrate parameter, of a total of 151 private deep wells located in agricultural areas at the Tietê-Jacaré basin, registered at the São Paulo State Water Department. The integrated data, grouped for each Aquifer, has been submitted to basic statistics analysis, calculating its averages, medium, maximum and minimums. The medium ones were used as a reference, for comparison to the orientating values of quality reference, prevention and intervention. Of general form, from the results of the existing analyses, it is observed that the Nitrate concentrations are low, finding higher values in wells that take water from Bauru and Serra Geral Aquifers. None of the raised concentrations were above the national drinking water standard, however, the occurrence of nitrate concentrations above the prevention value deserves attention, indicating alteration on natural balance, mainly for human influence. The wells and their nitrate concentrations were located on a Tietê-Jacaré land use map, through which the ones located in sugar cane areas were identified. The nitrate data for those wells on sugar cane production areas were submitted, separately, to another basic statistics analysis, calculating the averages, medium, maximum and minimum, for comparison with the other wells located in areas with different land use types. On average, the concentrations of the wells in sugar cane area are higher than the concentrations for other wells, especially for the Bauru and Guarani Aquifers. In general, there are increasing concentrations throughout time, indicating the need for continuous monitoring for the nitrate parameter, beyond the establishment of preventive actions to avoid nitrate pollution.
Keywords: Águas subterrâneas; Contaminação difusa; Nitrato; Atividade agrícola; Tietê/Jacaré, Bacia (SP); Groundwater; Diffuse contamination; Nitrate; Agricultural activities; Tietê-Jacaré; Hydrographic basin; ENGENHARIAS